Interactive function based shape modelling - Alexei Sourin (2008)
In this project we have addressed interactive shape modelling problem using the function-based approach, where geometric shapes and their properties are defined with mathematical functions. Interactive modification of the function model with concurrent visualisation of the respective polygonal mesh provided us both the interactivity and any required level of detail resulting in photo-realistic appearance of the shapes. We introduced geometric operators to represent interactive modifications of geometry and appearance of the shapes. Mathematically the same functions are used for defining the shape?s geometry as well as colours, which can be interactively applied to it. Any of the operators involved in creating the shape can be edited, modified or removed at any time thus allowing for a great flexibility of the modelling pipeline and opening prospects for efficient reusing and improving of the models previously created.